Studi Perilaku Konsumen Minum Teh dalam Gaya Hidup Berdasarkan Kelas Sosial untuk Membudayakan Teh Bagian dari Wisata Kuliner (Studi Wilayah Jakarta Selatan dan Bogor) (Jurnal Ilmiah Pariwisata; Vol 20 No 2 (2015), 2015)
Drinking tea in Indonesia according to the literature, culture and history has a habit and populist. But in statistical data consumption rate is still low (0.2 kg / capita / year) compared with the sequence as a producer of tea in the world's fifth largest. From a business standpoint it can be seen not many restaurants that offer the main dish of tea, different things with coffee. Among the existing reality, tea culture has been attempted by a restaurant in Jakarta and also in Bogor, West Java, with the concept of on-site cafe and elite with a market share above Based Social Class (Jakarta) and in Bogor with shop concepts and outlets established in complex with college students and consumers in the mall with a market share of all ages. At the restaurant in Jakarta, in the initial conditions of business development a reality more coffee than tea, this restaurant is able to bring in a 20/2-hour or 70 person / day. In Bogor, in the shop in the complex could be the arrival of the college day about 60 people, while at the mall about 25 per day. The phenomenon that happens to be very interesting when examined in terms of consumer behavior in order to make a cup of tea as a culture among Based Social Class / urban and lower classes, so as to increase the prestige of the tea itself, and can be part of a culinary tour of Indonesia
Keywords: consumer behavior , lifestyle , social class , drinking tea, culinary